Clinical efficacy and safety of proton radiotherapy for ocular conjunctival malignancies: a systematic review and meta-analysis - Zheng, Tingwei; Wang, Dandan; Miao, Yuxin; Dong, Meng; Liu, Qin; Zhang, Qiuning; Bai, Huiling; Luo, Hongtao; Li, Meixuan (Frontiers in Public Health, 2025)
ObjectiveThe use of proton beam therapy (PBT) for treating ocular conjunctival malignancies is on the rise across numerous medical centers. This study conducts a systematic review and meta-analysis to assess the effectiveness and safety of PBT in treating malignant conjunctival tumors.MethodsWe searched for studies on PBT for ocular conjunctival malignancies in PubMed, Embase, Cochrane Library, and Web of Science (WoS) databases up to November 25, 2023. Studies were selected and data were extracted by two independent reviewers based on pre-established inclusion and exclusion criteria. The quality of evidence was assessed using the GRADE method. Meta-analysis was performed using STATA version 16.0.ResultsAn initial search yielded 586 articles, from which six retrospective case series studies were selected involving 291 patients with ocular conjunctival malignancies, including 240 cases of conjunctival melanoma and 51 cases of conjunctival squamous cell carcinoma (SCC). Meta-analysis with a random-effects model showed that PBT is effective and relatively safe, with 2-, 4-, and 5-year overall survival (OS) rates of 98% (95% CI 95–102%), 87% (95% CI 69–104%), and 78% (95% CI 70–87%) respectively. Reported toxicity rates included 19% for cataracts, 10% for glaucoma, 5% for lacrimal stenosis, 52% for sicca symptoms, and 11% for limbal stem cell deficiency. The GRADE assessment yielded a low certainty of evidence.ConclusionsProton therapy offers a viable alternative treatment for patients with conjunctival malignancies, with acceptable treatment-related toxicity rates.